2024
DOI: 10.1111/jvim.16991
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous remission and relapse of diabetes mellitus in a male dog

Mariola B. Rak,
Chen Gilor,
Stijn J. M. Niessen
et al.

Abstract: An 8‐year‐old male neutered Miniature Schnauzer was diagnosed with diabetes mellitus based on fasting hyperglycemia and glucosuria after a 2‐week history of polydipsia and periuria, in line with the Agreeing Language in Veterinary Endocrinology consensus definition. Treatment of insulin and dietary management was initiated. The insulin dose was gradually reduced and eventually discontinued over the next year based on spot blood glucose concentrations that revealed euglycemia or hypoglycemia. After discontinuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…Por outro lado, a remissão do Diabetes Melittus Canino (DMC) é considerada um evento raro, mas é possível quando seu diagnóstico está relacionado a fatores de resistência a ação da insulina, principalmente, aqueles associados aos ciclos hormonais da gestação, do estro e suas complicações como hiperplasia endometrial cística, piometra e síndrome do ovário remanescente (Fall et al, 2007;Feldman et al, 2014;Pöppl et al, 2013;Rak et al, 2024).…”
Section: Discussionunclassified
“…Por outro lado, a remissão do Diabetes Melittus Canino (DMC) é considerada um evento raro, mas é possível quando seu diagnóstico está relacionado a fatores de resistência a ação da insulina, principalmente, aqueles associados aos ciclos hormonais da gestação, do estro e suas complicações como hiperplasia endometrial cística, piometra e síndrome do ovário remanescente (Fall et al, 2007;Feldman et al, 2014;Pöppl et al, 2013;Rak et al, 2024).…”
Section: Discussionunclassified
“…Eventually, the use of aglepristone to block P4 effects by the end of estrus [154] could also be considered as a preventive measure in highly susceptible bitches. Notwithstanding, the recent characterization of diabetes remission in a male dog suggested that much of the beta-cell biology is still to be unraveled in canine diabetology [1,2,187]. Many owners do not agree with spaying their dogs, and in these cases, other ways to try to prevent PRDM are welcome.…”
Section: Appliable Preventive Measuresmentioning
confidence: 99%